Cloud computing explained. - Rhoton, John, ....- ([s.l.] : Recursive, 2010)
Cloud Computing Explained provides an overview of Cloud Computing in an enterprise environment. There is a tremendous amount of enthusiasm around cloud-based solutions and services as well as the cost-savings and flexibility that they can provide. It is imperative that all senior technologists have a solid understanding of the ramifications of cloud computing since its impact is likely to permeate the entire IT landscape. However, it is not trivial to introduce a fundamentally different service-delivery paradigm into an existing enterprise architecture. This book describes the benefits and challenges of Cloud Computing and then leads the reader through the process of assessing the suitability of a cloud-based approach for a given situation, calculating and justifying the investment that is required to transform the process or application, and then developing a solid design that considers the implementation as well as the ongoing operations and governance required to maintain the solution in a partially outsourced delivery model.